2012
DOI: 10.1159/000341446
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis and Growth Arrest in Human Breast Carcinoma Cells by a Snake (Walterinnesia aegyptia) Venom Combined With Silica Nanoparticles: Crosstalk Between Bcl2 and Caspase 3

Abstract: We recently demonstrated that the snake venom extracted from Walterinnesia aegyptia (WEV) either alone or combined with silica nanoparticles (WEV+NP) enhanced the proliferation of mice immune cells and simultaneously decreased the proliferation of human breast carcinoma cell line (MDA-MB-231). However, the molecular mechanism of how this venom induced growth arrest of breast cancer cells has not been studied. In this context, we extended our study to evaluate the anti-tumor potential of WEV and WEV+NP on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…According to recent study, snake venom extracted from Walterinessia aegyptia (WEV), alone or in combination with silica nano-particles can decrease the proliferation of human breast carcinoma cell line (MDA-MB-231). In this study, decreased expression of Bcl-2 and enhanced activation of caspase-3 has been found when breast cancer cell line was treated with WEV along with nano-particle and also showed significant reduction in actin polymerization and cytoskeletal rearrangement but it was not the case with non-cancer cell line (Al-Sadoon et al, 2012).…”
Section: Anticancer Activity Of Snake Venommentioning
confidence: 64%
“…According to recent study, snake venom extracted from Walterinessia aegyptia (WEV), alone or in combination with silica nano-particles can decrease the proliferation of human breast carcinoma cell line (MDA-MB-231). In this study, decreased expression of Bcl-2 and enhanced activation of caspase-3 has been found when breast cancer cell line was treated with WEV along with nano-particle and also showed significant reduction in actin polymerization and cytoskeletal rearrangement but it was not the case with non-cancer cell line (Al-Sadoon et al, 2012).…”
Section: Anticancer Activity Of Snake Venommentioning
confidence: 64%
“…Furthermore, silica NPs also biologically amplify the antineoplastic effects of a traditional snake venom medicine against breast and prostate cancer as well as multiple myeloma [162,178,179]. Extensive nanoscience evidence demonstrates not only biological amplification effects of nanosilica, but also bottom up self-assembly of silica-based nanostructures using biological materials as templates [180].…”
Section: Experimental Questionsmentioning
confidence: 99%
“…Some evidence suggests that including different sizes of the same source material NPs in antennas or multi-component nano-ensembles leads to better self-similar amplification of effects [138,142,143,[156][157][158][159][160], including stochastic resonance [139,142,161]. For higher potencies made traditionally in glass-contained liquids, the release and presence of nanosilica and/or nanosilicon in solution from succussions in glassware could contribute a drug-delivery vehicle and a biological [34,37,162], microelectronic and photonic amplifier [163,164].Some homeopathically-manufactured nanostructures from bacteria emit characteristic electromagnetic signals that can be detected and recorded [165]. Agitation of the solutions during manufacturing is necessary to generate such phenomena.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been reported in a study on growth inhibition of breast cancer cells with snake venom. 37 The phenomenon of cell cycle arrest has been used as a therapeutic tool to inhibit tumor progression in in vitro studies. 38 The mechanism for reduced DNA replication could be attributed to the "shutting down" of some cancer survival trails, including the NF-ÎșB signaling cascade.…”
mentioning
confidence: 99%